Water banking in Idaho - Rigby, Richard M., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
Some irrigation projects in the Pacific Northwest are 50 - 70 years old. Storage and delivery facilities were originally constructed based on the best available data and permanent water allocations were made to meet the identified agricultural water needs. The intervening years have brought changes in farming practices and associated water needs, as well as the identification of new competing demands for water. When water supplies are fully allocated to existing users, the opportunities to develop new uses may be very limited. Water banking provides an opportunity to temporarily transfer water from an established water right holder to another. Two water banks are presently functioning within the State of Idaho. These banks enable water users to transfer their storage entitlements to other users. Water banking is expressly authorized by Idaho law and the existing water banks function with the support and assistance of the Bureau of Reclamation and the Idaho Department of Water Resources.
USCID regional meetings -- 1989
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.